(3PGJ GdMdd hegGI Gdcdds - (3Ydj Hf eMeO Hf YHO GdUeO GdgeOGfj GdeUQj GdSNGhj GdTGaYj, CHh GdMSf, Yde GdOjf,J (B643 (3g` s
(3ChdgG (B:s
(3eWdYgG(B: (3HMeO Gddg QH GdYGdejfG hQH GdYQT CHOkG eSJYjfG s
(3YdjgG ELGRI HNW GdeDda eDQNI SfI (B635s
(3hgj efXheIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B209s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B539 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B468 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs